1974
DOI: 10.1021/j100602a002
|View full text |Cite
|
Sign up to set email alerts
|

Fall-off behavior of a thermal unimolecular system in the presence of a weak collider inert bath gas

Abstract: The behavior of the thermal unimolecular methyl isocyanide isomerization system has been examined at 245°over the whole range of fall-off from the low to high pressure regions at infinite dilution by the weak collider, helium, and by the strong collider, butane. The pressure displacement factor for the helium fall-off curve relative to the behavior of the pure substrate increases with decreasing order of reaction, as predicted. A comparison with theoretical calculations indicates that the collisional behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Earlier, trajectory calculations done by Bunker and Hase using collisional energies of 293 to 837 kJ mol –1 showed non-RRKM unimolecular kinetics for CH 3 NC. This theoretical finding is potentially not relevant to thermal experiments since the collisional energies are so far above that at the reaction threshold.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier, trajectory calculations done by Bunker and Hase using collisional energies of 293 to 837 kJ mol –1 showed non-RRKM unimolecular kinetics for CH 3 NC. This theoretical finding is potentially not relevant to thermal experiments since the collisional energies are so far above that at the reaction threshold.…”
mentioning
confidence: 92%
“…The isomerization of methyl isocyanide (CH 3 NC) to acetonitrile (CH 3 CN) is a prototypical homogeneous unimolecular reaction that has long been studied with various experimental techniques. A half century ago, Rabinovitch and co-workers measured thermal rate constants over a wide range of temperatures and pressures in the falloff region. These authors reported an activation energy of 160.7 kJ mol –1 at the high-pressure limit and an Arrhenius pre-exponential factor of 10 13.5 s –1 , results that were verified by subsequent experimental studies. In addition, on the basis of models and statistical Rice–Ramsperger–Kassel–Marcus (RRKM) theory, , Rabinovitch and co-workers were able to satisfactorily reproduce the measured rate constants in the falloff region (within a factor of 2) .…”
mentioning
confidence: 99%